Profit Planning Analysis with Break Even Point Approach at PT. Sinar Jaya - Bisyarah, Sania; Elizabeth S, Sri Novi (International Journal of Global Operations Research, 2024)
Sales management is important for a company to control profitability and avoid the risk of loss.  In reality, companies are often faced with the possibility of loss and the ability to manage sales can affect the magnitude of this risk. Break Even Point (BEP) analysis can be an effective strategy to determine the minimum sales amount so that the company avoids losses. In this study, analyzed sales at PT Sinar Jaya using BEP analysis for the period January to December 2023. The results of the analysis show that the company is consistently able to achieve BEP and earn profits above 7% every month which reflects operational efficiency in profit stability. In addition, the Margin of Safety (MoS) value which is always above 20%, with a peak reaching 70%, shows that the company has strong protection against risk.